Twitter Use by Politicians Across States in India - Shekhawat, Gazal; Singh, Parantak; Grover, Rynaa; Dash, Saloni; Negi, Himani; Sharma, Ankur; Sagarika, Somya; Pal, Joyojeet (2021)
This report examines the use of Twitter by politicians throughout the various states of India. Using a manually annotated database of 37633 politicians and 16522 influencers throughout India, we present a picture of the key players and trends in Twitter use by politicians in India. The document focuses on three main aspects of political Twitter engagement. First, we look at the volume of engagement, particularly by party – on levels of engagement and the use of language by politicians over time. Second, we examine the dominance of individual politicians by state – who are the key players in each location in terms their overall following and engagement, and finally, we look at the engagement of politicians with influencers and journalists in India. The report presents a picture of the Twitter footprint of politicians, its growth over time, and the patterns of engagement between politicians and key social media influencers and newspapers by state.